Understanding the Leadership of Khulafa Ar- Rashidin and the Practice of Noble Values - Zulkifli, Hafizhah; Azman, Nor Alniza; Razak, Khadijah Abdul (International Journal of Psychosocial Rehabilitation, 2020)
The decrease of moral values among Muslim youth apparently not because of the imperfections of Islamic teachings but they are misguided in making decisions by choosing the wrong idols and following the wrong believes. Therefore, the main purpose of this study was to identify the level of students' understanding of Khulafa Ar- Rashidin's leadership as a Role Model, the level of the practice of noble values among students and the correlation between understanding khulafa ar-rashidin and practice of noble values. This study used survey research design and the samples are 322 respondent of form two students. The analysis data using SPSS 23.0 software involved descriptive analysis and inference analysis. The pilot test showed that the reliability level is high about 0.9. The results show that the level of students' understanding of Khulafa Ar-Rashidin's leadership is at a high level. Meanwhile, the students' level of the practice of noble values is at a moderate level. The results of t-test show that there is a significant different in the level of understanding khulafa ar Rashidin while there is no significant different in the level of students’ practice of noble values based on gender. The results of the Pearson Correlation analysis show that there is a positive relationship between the understanding of Khulafa Ar-Rashidin's leadership and the practice noble values among students. The implications of this study are to provide guidance to teachers to focus on teaching more effectively in the application of noble values to students, especially topics related to Islamic leaders. This is because many of the lessons can be learned from such figures as imitating their personalities, thus encouraging students to make Khulafa Ar- Rasyidin a Role Model in their daily lives.